Novel synthesis of SrBi2Nb2O9 powders from hydroxide precursors - Gupta, Upendra Nath; Rao, Koteswara; Pradhan, Sivaram; Jha, Ratnesh Kumar; Muthurajan, Harries; Ravi, Venkat (International Journal of Applied Ceramic Technology, 2008)
Simple hydroxide precursors were used for the first time for the synthesis of a typical Aurivillius compound (SrBi2Nb2O9 (SBN)) at a low temperature. This method is very advantageous because it circumvents the use of SrCO3 in the case of conventional ceramics as well in the coprecipitation methods, thereby lowering the formation of the product phase. Commercially purchased strontium hydroxide is mixed thoroughly with freshly precipitated bismuth and niobium hydroxides in a stoichiometric ratio and heated at different temperatures ranging from 100 degrees C to 750 degrees C for 12 h. The sequence of the reaction and evolution of the product phase was monitored by X-ray diffraction (XRD) studies by recording the XRD for samples calcined at different temperatures. The incipient SBN phase begins to form at temperatures as low as 400 degrees C, and phase formation was complete only at 650 degrees C as revealed by the XRD observations. The differential thermal/thermogravimetric analyses) also corroborate this result. The morphology and average particle size of these powders were investigated by transmission electron microscopy studies.